Rich People Problems : A Novel - Kwan, Kevin, 1973- (New York, NY : ANCHOR BOOKS, 2018)
When Nicholas Young hears that his grandmother, Su Yi, is on her deathbed, he rushes to be by her bedside but he's not alone. The entire Shang-Young clan has convened from all corners of the globe to stake claim on their matriarch s massive fortune. With each family member vying to inherit Tyersall Park a trophy estate on 64 prime acres in the heart of Singapore Nicholas s childhood home turns into a hotbed of speculation and sabotage. As her relatives fight over heirlooms, Astrid Leong is at the center of her own storm, desperately in love with her old sweetheart Charlie Wu, but tormented by her ex-husband a man hell bent on destroying Astrid s reputation and relationship. Meanwhile Kitty Pong, married to China s second richest man, billionaire Jack Bing, still feels second best next to her new step-daughter, famous fashionista Colette Bing. A sweeping novel that takes us from the elegantly appointed mansions of Manila to the secluded private islands in the Sulu Sea, from a kidnapping at Hong Kong s most elite private school to a surprise marriage proposal at an Indian palace, caught on camera by the telephoto lenses of paparazzi, Kevin Kwan's hilarious, gloriously wicked new novel reveals the long-buried secrets of Asia's most privileged families and their rich people problems.
Keywords: American fiction; Rich people -- Fiction; Upper class -- Fiction; Humorous fiction